2020
DOI: 10.1111/os.12843
|View full text |Cite
|
Sign up to set email alerts
|

One‐Stage Total Hip Arthroplasty with Modular S‐ROM Stem for Patients with Bilateral Crowe Type IV Developmental Dysplasia

Abstract: The aim of the present paper was to evaluate the results of one-stage total hip arthroplasty (THA) for patients with bilateral Crowe type IV developmental dysplasia of the hip (DDH). Methods: Data for 58 patients (116 hips) with bilateral Crowe type IV DDH who had one-stage THA performed by the same surgeon during the period of April 2008 to February 2019 were retrospectively reviewed. The mean age of the patients was 37.3 years; 5 were men and 53 were women. All patients underwent THA through the posterolater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…It has been reported that subtrochanteric osteotomy is usually necessary for some high dislocation hips such as Crowe type IV DDH. 13 , 16 , 37 However, in our study, some of these varus hips might avoid osteotomy by matching the metaphyseal with a conical sleeve, benefiting from the deeper implantation of stems, which is worthy of further study ( Figure 5 ).
Figure 5 Preoperative ( A ) the deformity of coxa vara is associated with a high dislocation and a narrow and straight medullary cavity, which might be undergone the subtrochanteric osteotomy.
…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…It has been reported that subtrochanteric osteotomy is usually necessary for some high dislocation hips such as Crowe type IV DDH. 13 , 16 , 37 However, in our study, some of these varus hips might avoid osteotomy by matching the metaphyseal with a conical sleeve, benefiting from the deeper implantation of stems, which is worthy of further study ( Figure 5 ).
Figure 5 Preoperative ( A ) the deformity of coxa vara is associated with a high dislocation and a narrow and straight medullary cavity, which might be undergone the subtrochanteric osteotomy.
…”
Section: Discussionmentioning
confidence: 79%
“…First, the modularity of the SROM allowed relatively free adjustment of the abnormal femoral anteversion by rotation between the stem and sleeve to avoid the obstruction of the overhanging greater trochanter, protecting the abductor tendon insertion and decreasing instability. 2 , 12 , 14 Second, different sizes of sleeves and stems could appropriately match the different morphologies of the medullary cavity to generate maximal contact, which decreased the occurrence of proximal bone loss due to stress shielding, 13 , 14 and alter the FO and length to achieve strong initial fixation. As a decrease in FO is common due to a stem NSA became greater than the native value after THA, 8 , 21 an increased offset is necessary during surgery to reduce the load of the abductor, which has been showed in our radiographic results, and it decreased the joint reaction force, improving limp and enhancing the survival of the artificial join.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skeletal deformity of Crowe type IV DDH occurs not only in the hip joint but in the pelvis and the spine, which is reflected in pathological compensatory sagittal pelvic anterior tilt and lumbar lordosis owing to the inadequate support for bilateral anatomic alacetabulum without femoral heads. Total hip arthroplasty (THA) could eliminate deformities of the hip and establish a new spine‐pelvic sagittal balance, which is the most effective solution to this condition 10–13 …”
Section: Introductionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) could eliminate deformities of the hip and establish a new spine-pelvic sagittal balance, which is the most effective solution to this condition. [10][11][12][13] Change of pelvic sagittal tilt (PST) before and after THA caused by DDH reveals that operations have effects on the pelvic sagittal plane and the anteversion angle of the acetabulum. [14][15][16][17][18][19][20] Though Blondel et al 19 reported no significant change in pelvic morphology after THA for unilateral OA with a 3-year follow-up, and Maratt et al 21 studied 138 patients with unilateral OA before and 6 weeks after THA and found that the change of pelvic tilt in all patients had no significant differences.…”
Section: Introductionmentioning
confidence: 99%